PENERAPAN METODE PEMBELAJARAN BERBASIS MASALAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK PGRI PEKANBARU - Amaluddin, Muhammad Rizqi (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2022)
The problem-based learning method is an active learning method that can be applied by educators when carrying out the learning process in class. Through problem-based learning, students will be invited to study independently, seek information related to problems, conduct discussions, seek solutions to solving problems, and be able to conclude. This article discusses the application of problem-based learning methods to the subject of Islamic Religious Education at SMK PGRI Pekanbaru City. This study aims to find out how to apply problem-based learning methods, the steps in applying problem-based learning methods, and the factors that support and hinder the application of problem-based learning methods in Islamic Education subjects at SMK PGRI Pekanbaru City. The method used in this research is field research through a qualitative approach with descriptive analysis of the data obtained through observation and interviews. The results of the research in this article are that educators can apply problem-based learning methods through appropriate materials, educators can apply steps and guide students with problem-based learning methods and educators can overcome some of the obstacles encountered in implementing problem-based learning methods.